2008
DOI: 10.1109/led.2008.922978
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of Statistical Variability Sources in a 45-nm Technological Node LP N-MOSFET

Abstract: Abstract-A quantitative evaluation of the contributions of different sources of statistical variability, including the contribution from the polysilicon gate, is provided for a low-power bulk N-MOSFET corresponding to the 45-nm technology generation. This is based on a joint study including both experimental measurements and "atomistic" simulations on the same fully calibrated device. The position of the Fermi-level pinning in the polysilicon bandgap that takes place along grain boundaries was evaluated, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(30 citation statements)
references
References 15 publications
0
30
0
Order By: Relevance
“…[1][2][3][4][5] Properties of electrode/NW contact-interfaces are of particular interest [6][7][8][9][10] due to the potential application of quasi-one-dimensional materials into future nanosensing and nanoelectronic devices. 11 It has been proposed by theory that Fermi level pinning effects, which frequently hinder the performance of planar devices, 12 are expected to be strongly reduced in side contacts to NW channels due to their confined geometry. 13,14 Although several studies regarding the contact-resistivity in semiconducting NW devices can be found, [6][7][8][9][10] an analysis addressing both the contact-interface properties and also verifying the plausibility of common bulk-based extrapolation methods is to-date not presented.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] Properties of electrode/NW contact-interfaces are of particular interest [6][7][8][9][10] due to the potential application of quasi-one-dimensional materials into future nanosensing and nanoelectronic devices. 11 It has been proposed by theory that Fermi level pinning effects, which frequently hinder the performance of planar devices, 12 are expected to be strongly reduced in side contacts to NW channels due to their confined geometry. 13,14 Although several studies regarding the contact-resistivity in semiconducting NW devices can be found, [6][7][8][9][10] an analysis addressing both the contact-interface properties and also verifying the plausibility of common bulk-based extrapolation methods is to-date not presented.…”
mentioning
confidence: 99%
“…The simulator is meticulously calibrated and validated in respect of statistical variability simulations and measurements at 45/40 nm [19], and at 32/28 nm technology generations [14]. It has been demonstrated that that RDD, LER and MGG are major statistical variability sources in 32/28nm high-k/metal gate bulk CMOS technology.…”
Section: Simulation Methodologymentioning
confidence: 99%
“…This is based on meticulous validation of our simulation technology in respect of 45/40 nm [19] and 32/28-nm technology [14]. This paper also goes beyond most of the previously published simulation and measurement results, reporting a systematic study on the impact of geometry, substrate bias and temperature on the statistical variability of carefully designed 'template' 25 nm gate-length MOSFETs meeting the specifications of 20 nm CMOS.…”
Section: Introductionmentioning
confidence: 97%
“…Details about the device structure and doping profiles are published elsewhere [12,13]. We simulate NBTI variability associated with fixed/trapped random positive charges in concert with all other variability sources relevant for this technology.…”
Section: Simulation Methodologymentioning
confidence: 99%